PEMBERIAN INISIASI MENYUSU DINI PADA BAYI BARU LAHIR - Arlin Adam; Andi Alim; Novi Purnama Sari (Politeknik Kesehatan Kemenkes Mamuju, 2016)
Provision of Early Initiation of Breastfeeding (IMD) to newborns in Indonesia is still relatively more low. Early Initiation of Breastfeeding can increase potential success of exclusive breastfeeding for 6 months. Found 40% of infant deaths occur in the first month of life. The infant mortality can be reduced by up to 22% with action of Early Initiation Breastfeeding. This study aimed to analyze the influence of knowledge, support health, and social culture of the provision of Early Initiation of Breastfeeding newborn. This research was conducted at the General Hospital of Makassar to the entire population that has been doing deliveries, with a total sample of 100 respondents. Research shows that there is a relationship between the mother's knowledge by giving Early Initiation of Breastfeeding (p = 0.000). There is a relationship between support services to the administration of Early Initiation of Breast feeding (p = 0.000). There was no relationship between the social and cultural perspectives giving Early Initiation of Breastfeeding (p = 1,000). Enough knowledge about the provision of Early Initiation of Breastfeeding is a need for being able to reduce infant mortality. Health workers support the Early Initiation of Breastfeeding is an appropriate step to encourage mothers to give Early Initiation of Breastfeeding. Social effects of culture against early initiation of breastfeeding sometimes become an obstacle to the provision of Early Initiation of Breastfeeding.